Circulating Factors in Trauma Plasma Activate Specific Human Immune Cell Subsets. Issue 4 (April 2020) - Cahill, Laura A.; Guo, Fei; Nguyen, Jennifer; Zhang, Fan; Seshadri, Anupamaa; Keegan, Joshua; Hauser, Carl J.; Otterbein, Leo E.; Robson, Simon; Shaefi, Shahzad; Yaffe, Michael B.; Lederer, James A.
Highlights: Early trauma plasma increases CD11c+ natural killer cells. CD8+ T cells are increased by circulating factors in trauma plasma. Increased pro-inflammatory cytokines in trauma plasma are associated with at an earlier timepoint. Abstract: Background: Trauma causes tissue injury that results in the release of damage associated molecular patterns (DAMPs) and other mediators at the site of injury and systemically. Such mediators disrupt immune system homeostasis and may activate multicellular immune responses with downstream complications such as the development of infections and sepsis. To characterize these alterations, we used time-of-flight mass cytometry to determine how trauma plasma affects normal peripheral blood mononuclear cell (PBMC) activation to gain insights into the kinetics and nature of trauma-induced circulating factors on human immune cell populations. A better understanding of the components that activate cells in trauma may aid in the discovery of therapeutic targets. Methods: PBMCs from healthy volunteers were cultured with 5% plasma (healthy, trauma-1day, or trauma-3day) or known DAMPs for 24 h. Samples were stained with a broad immunophenotyping CyTOF antibody panel. Multiplex (Luminex) cytokine assays were used to measure differences in multiple cytokine levels in healthy and trauma plasma samples. Results: Plasma from day 1, but not day 3 trauma patients induced the acute expansion of CD11c+ NK cells and CD73+/CCR7+ CD8 T cell subpopulations. Additionally, trauma plasma did not induce CD4+ T cell expansion but did cause a phenotypic shift towards CD38+/CCR7+ expressing CD4+ T cells. Multiplex analysis of cytokines by Luminex showed increased levels of IL-1RA, IL-6 and IL-15 in trauma-1day plasma. Similar to trauma day 1 plasma, PBMC stimulation with known DAMPs showed activation and expansion of CD11c+ NK cells. Conclusions: We hypothesized that circulating factors in trauma plasma would induce phenotypic activation of normal human immune cell subsets. Using an unbiased approach, we identified specific changes in immune cell subsets that respond to trauma plasma. Additionally, CD11c+ NK cells expanded in response to DAMPs and LPS, suggesting they may also be responding to similar components in trauma plasma. Collectively, our data demonstrate that the normal PBMC response to trauma plasma involves marked changes in specific subsets of NK and CD8+ T cell populations. Future studies will target the function of these trauma plasma reactive immune cell subsets. These findings have important implications for the field of acute traumatic injuries.